Hypothermic circulatory arrest time affects neurological outcomes of frozen elephant trunk for acute type A aortic dissection: A systematic review and meta‐analysis. Issue 9 (14th June 2021) - Mousavizadeh, Mostafa; Daliri, Mahdi; Aljadayel, Hadi Abo; Mohammed, Idhrees; Rezaei, Yousef; Bashir, Mohamad; Hosseini, Saeid
Abstract: Background: The treatment of complex thoracic aorta pathologies remains a challenge for cardiovascular surgeons. After introducing Frozen Elephant Trunk (FET), a significant evolution of surgical techniques has been achieved. The present meta‐analysis aimed to assess the efficacy of FET in acute type A aortic dissection (ATAAD) and the effect of circulatory arrest time on post‐operative neurologic outcomes. Methods: A standard Preferred Reporting Items for Systematic Reviews and Meta‐Analyses search was conducted for all observational studies of patients diagnosed with ATAAD undergoing total arch replacement with FET reporting in‐hospital mortality, bleeding, and neurological outcomes. A random‐effect meta‐analysis was performed using STATA software (StataCorp, TX, USA). Results: Thirty‐five studies were eligible for the present meta‐analysis, including 3211 patients with ATAAD who underwent total arch replacement with FET. The pooled estimate for in‐hospital mortality, postoperative stroke, and spinal cord injury were 7% (95% CI 5 – 9; I 2  = 68.65%), 5% (95% CI 4 – 7; I 2  = 63.93%), and 3% (95% CI 2 – 4; I 2  = 19.56%), respectively. Univariate meta‐regression revealed that with increasing the duration of hypothermic circulatory arrest time, the effect sizes for postoperative stroke and SCI enhances. Conclusions: It seems that employing the FET procedure for acute type A dissection is associated with acceptable neurologic outcomes and a similar mortality rate comparing with other aorta pathologies. Besides, increasing hypothermic circulation arrest time appears to be a significant predictor of adverse neurologic outcomes after FET.